Knowledge about schizophrenia, insight into illness, and internalized stigma and their associated factors among people diagnosed with schizophrenia in a long‐term care facility. Issue 1 (5th June 2020) - Alhadidi, Majdi; Abdullah, Khatijah Lim; Tang, Li Yoong; Danaee, Mahmoud; Al Hadid, Lourance Abdel Razzaq
Abstract: Purpose: This study assessed the level of knowledge about schizophrenia, insight into illness, and internalized stigma and their associated factors among patients with schizophrenia in Jordan. Design and Methods: A cross‐sectional survey was conducted on 135 patients diagnosed with schizophrenia, who had been admitted to the largest psychiatric hospital in Jordan. Findings: The participants had a low level of knowledge, insight, and a high level of internalized stigma. No correlation was found between these variables. Meanwhile, the educational level and vacation were found to be predictors of knowledge. Practice Implications: This can help psychiatric nurses to identify which area needs to be improved to ensure the best service and care is provided to patients diagnosed with schizophrenia.